How digital signal processing aids analog filter design - Ramaswamy, Ramkumar (Engineering cases, 2012)
With the increasing sophistication of drag-and-drop DSP design tools that abstract away the details of discrete-time processing mathematics and eliminate the need for programming, it is often possible to treat a DSP platform as a powerful "live" prototyping and simulation tool for traditional analog filter design without having to bear the burden of a paradigm shift. What is more important and exciting is that the simulated filter can be mapped transparently to an analog realization without further redesign or used as a digital filter as is.